Molecular dynamics study on the mechanism of polynucleotide encapsulation by chitosan - Jia-Wei Shen; Jiachen Li; Zhennan Zhao; Li Zhang; Guoteng Peng; Lijun Liang (Scientific Reports, 2017)
Abstract The safe and effective delivery of therapeutic genes into target cell interiors is of great importance in gene therapy. Chitosan has been extensively studied as a gene delivery carrier due to its good biocompatibility and biodegradability. Understanding the atomic interaction mechanism between chitosan and DNA is important in the design and application of chitosan-based drug and gene delivery systems. In this work, the interactions between single-stranded polynucleotides and different types of chitosan were systematically investigated by using molecular dynamics (MD) simulation. Our results demonstrate that the functional groups of chitosan, the types of base and length of polynucleotides regulate the interaction behavior between chitosan and polynucleotides. The encapsulation capacity of polynucleotide by chitosan is mainly balanced by two factors: the strength of polynucleotide binding to chitosan and the tendency of self-aggregation of polynucleotide in the solution. For –NH3 + chitosan, due to the strong electrostatic interaction, especially the H-bond between –NH3 + groups in chitosan and phosphate groups in polynucleotide, the aggregation effect could be partially eliminated. The good dispersal capacity of polynucleotides may improve the encapsulation of polynucleotides by chitosan, and hence increase the delivery and transfection efficiency of chitosan-based gene carrier.